Embarazo abdominal a término: reporte de un caso Abdominal pregnancy at term: case report - Mario Díaz González (Revista Colombiana de Obstetricia y Ginecología, 2002)
El embarazo abdominal es poco frecuente y está asociado con alta mortalidad materna y fetal. Es raro que llegue al término y mucho más obtener un recién nacido en buenas condiciones. Un caso de embarazo abdominal a término (40,5 semanas), el cual fue atendido exitosamente en la Clínica General del Norte en Barranquilla, Colombia por el Departamento de Ginecología y Obstetricia: Paciente de 33 años G2P1 con diagnóstico de ingreso de embarazo de 40,5 semanas, DPPNI y pre-eclampsia; a quien se le hizo un diagnóstico transoperatorio de embarazo abdominal a término, con producto de la gestación en buenas condiciones. Abdominal pregnancy is uncommon and associated with higher fetal and maternal mortality. It is rare to grow to term and furthermore obtain a newborn in good conditions. A case of abdominal pregnancy at term ( 40,5 weeks) which was successfully treated in the Clinica General del Norte, Barranquilla, Colombia, by the obstetrics and gynecologist department; was an obstetric patient of 33 years old, G2P1 with initial diagnosis of 40,5 weeks of gestation, abruptio placentae and pre-eclampsia; with postoperative diagnosis of abdominal pregnancy at term with a newborn in good conditions. This article is a case report. It has a general interest for two reasons: 1) Its an uncommon event in obstetrics, the abdominal pregnancies with an alive fetus have very now frequency in the world. 2) A brief revision and how to confront this kind of cases is made.